Pengaruh Pemberian Eco-enzyme terhadap Pertumbuhan dan Perkembangan Tanaman Persea americana - Atika Okta Melisa (Jurnal Pendidikan Biologi Undiksha, 2024)
This research aims to find out the effect of giving eco-enzymes on the growth and development of avocado plants (Persea americana) as well as the optimum concentration that can be given to avocado plants (Persea americana). This study was quantitative research with CRD (Completely Randomized Design as experimental design. The difference test used was ANOVA and DMRT used as further tests. The results of the study showed that there was an effect of eco-enzyme on the growth and development of Persea americana. The results of the ANOVA test showed a significance value of 0.001 on the growth of plant length and 0.000 on the number of leaves. Both significance values ​​<0.05 which means that shown a significant effect. The optimum concentration was found in the P2 treatment, which was 5 mL/L with an average plant length of 31.5 cm and an average number of leaves of 15 strands.